PENGUKURAN PERTUMBUHAN EKONOMI KREATIF KOTA MALANG - Sri Palupi Prabandari; Franciska Yuniati; Dwi Maulidatuz (Bappeda Kota Malang, 2023)
Abstract: Creative economy is a concept to realize sustainable economic development based on creativity. Utilization of resources that are not only renewable, even unlimited, namely in the form of ideas, ideas, talents or talents and creativity. The creative economy is the creation of added value (economic, social, cultural, environmental) based on ideas born from the creativity of human resources (creative people) and based on the utilization of knowledge, including cultural and technological heritage. In creative and innovative words, the value of the goods/services produced is certainly of high selling value. Malang City has been designated by the Ministry of Tourism and Creative Economy (Kemenparekraf) as a creative city, where in this case Malang City carries out various innovations to support the creative economy. Malang City has 12,948 creative economy actors in Malang City. This is certainly a great potential for creative economic growth in the city of Malang. The results of the growth in the PDRB figure for the Creative Economy of Malang City in 2021 on the basis of constant prices experienced a significant increase, namely to 3.47% from -8.85% in 2020. This is because creative economy business actors were affected by the COVID-19 pandemic in 2020. Growth will increase in 2021 due to the economy in Malang City which is starting to recover and creative economy business actors starting to adapt to the normal era so that the GRDP value of the creative economy has increased. Keywords: Creative Economy, Malang City, GRDP.